Exploring the Experiences of Muslim Early Childhood Educators in Teaching Sexuality Education - Pratiwi, Hardiyanti; Suyanto, Slamet; Yarliani, Ikta (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2024)
Early childhood sexuality education is essential for safeguarding young children against inappropriate sexual content and potential abuse. This study underscores the importance of such education within the context of Muslim teachers. The primary objective of this research is to gain insights into the practical implementation of sexuality education during early childhood. The study encompasses the participation of 248 Muslim early childhood teachers. By collecting open-ended inquiries, analyzing responses verbatim, and categorizing the results, the research illuminates the multifaceted responsibilities of these teachers. Their roles include providing guidance on toileting, mitigating self-touch behaviors, addressing sexual curiosity, promoting genital health and hygiene, preventing sexual harassment, and recognizing the spectrum of gender roles. The findings highlight the urgency of developing a well-structured curriculum, fostering collaboration between parents and teachers, providing specialized teacher training, promoting a positive public perception of sexuality education, and ensuring substantial government involvement in early childhood sexual education.